'Thoroughly reforming them towards a healthy heart attitude': China's political re-education campaign in Xinjiang. - Zenz, Adrian (Central Asian Survey, 2019)
Since spring 2017, the Xinjiang Uyghur Autonomous Region in China has witnessed the emergence of an unprecedented re-education campaign. According to media and informant reports, untold thousands of Uyghurs and other Muslims have been and are being detained in clandestine political re-education facilities, with major implications for society, local economies and ethnic relations. Considering that the Chinese state is currently denying the very existence of these facilities, this paper investigates publicly available evidence from official sources, including government websites, media reports and other Chinese internet sources. First, it briefly charts the history and present context of political re-education. Second, it looks at the recent evolution of re-education in Xinjiang in the context of 'de-extremification' work. Finally, it evaluates detailed empirical evidence pertaining to the present re-education drive. With Xinjiang as the 'core hub' of the Belt and Road Initiative, Beijing appears determined to pursue a definitive solution to the Uyghur question.